Penerapan Undang-undang Nomor 32 Tahun 2009 Pasal 109 Tentang Perlindungan Dan Pengelolaan Lingkungan Hidup - Bara Firmansyah; Fenty Puluhulawa; Lisnawaty W. Badu (Perkara : Jurnal Ilmu Hukum dan Politik, 2024)
This research aims to determine the effectiveness of ownership of operational permits for wastewater disposal installations as factors inhibiting this effectiveness in the Randangan District Health Center. This research is a sociological or empirical study, with the aim of presenting as complete data as possible regarding the effectiveness of permit ownership for Community Health Centers in Randangan District, as stated in Law Number 32 of 2009. The types of data used include primary data and secondary data, and the data collection techniques used are field research and literature study. Based on the research in the results of the discussion, conclusions are drawn; Firstly, the Motolohu Community Health Center in Randangan District has been operating an IPAL since 2017 but until 2023 it has not received a permit from the Pohuwato Regency Environmental Service, even though according to the regulations, IPALs that have been operated must have a permit. Second, factors that hinder effectiveness include legal factors, law enforcement factors, legal advice and facilities, and community factors.